Rgis Boyer, La mort chez les anciens scandinaves, París, Les Belles Lettres, 1994, 241 pp. (Minerva, 2019)
Review: Rgis Boyer, La mort chez les anciens scandinaves, París, Les Belles Lettres, 1994, 241 pp.